The Application of Problem-Based Learning Model as an Effective Solution in Social Studies Learning in Elementary Schools - Lukman Ismail; Andi Nursida; Dinda Nurul Isnaeni; Jestin Erlangga (Indonesian Journal Publisher, 2025)
The main objective of this study is to present a conceptual study on the application of the Problem Based Learning (PBL) model as an innovative strategy to improve student learning outcomes in Social Studies (IPS). The Problem Based Learning (PBL) model is designed to hone students' critical thinking, analytical, creative, and collaborative skills in the process of solving problems oriented towards real-life situations, which in turn can encourage an increase in students' academic achievement. This study uses a library research approach by referring to various literature sources, scientific journals, and previous research results relevant to the implementation of the Problem Based Learning (PBL) model. The results of the research findings show that the application of the Problem Based Learning (PBL) model is effective in improving student learning outcomes in social studies. This model is implemented through group discussions and problem solving activities that are relevant to the daily lives of students, thereby stimulating active thinking and problem-solving skills. The findings in this study are expected to make a significant contribution, both theoretically and practically, to educators, researchers, and policymakers in developing more creative, participatory, and relevant learning strategies, as well as serving as a reference for other researchers who wish to develop similar research in the context of education. Keywords: Problem-Based Learning; Social Studies Education Learning Model; Effective Solutions